(untitled) (American Journal of Education and Technology, 2023)
ICTs have now become a buzzword in teaching and learning. Historically, technology has been developed to solve problems, improve living standards and increase productivity. In the educational context, the objectives of ICT are to increase productivity and solve teaching-learning problems. Information and communication technologies play a major role in shaping the new global economy and producing rapid changes in society. The purpose of the study is to find out the awareness level of various ICT devices, proficiency of ICT devices, and the usage of various ICT devices by the PG students. This study was descriptive research that adopts the survey method. Here the researcher used simple random sampling to select 50 samples. To conduct the present investigation, the researcher utilized a self-made questionnaire to gather data, it includes 32 items that are divided into three major dimensions on the basis of the research objectives. The researcher used Mean, SD, and t-tests for the statistical analysis of data. After analysis of the data this study found that there is a significant difference between male and female, and no significant difference between urban and rural PG students in the awareness level of various ICT devices. The two groups of students, namely male and female, differ significantly; the other two groups, urban and rural, do not differ significantly in terms of their proficiency in various ICT devices. The study also found that four groups of students namely male, female and urban, rural differ significantly in terms of the usage of various ICT devices.